2019
DOI: 10.3390/fi11090199
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the 3GPP V2X Architecture with Information-Centric Networking

Abstract: Vehicle-to-everything (V2X) communications allow a vehicle to interact with other vehicles and with communication parties in its vicinity (e.g., road-side units, pedestrian users, etc.) with the primary goal of making the driving and traveling experience safer, smarter and more comfortable. A wide set of V2X-tailored specifications have been identified by the Third Generation Partnership Project (3GPP) with focus on the design of architecture enhancements and a flexible air interface to ensure ultra-low latenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Extensive research has been going on with the suitability of different wireless technologies for V2X communication. Few researchers have suggested medium and long-range low-power wireless technologies like long range (LoRa) communication, Zigbee, BLE, and WIFI [11][12][13] On the other hand, researchers have adopted wireless technologies such as the Third Generation Partnership Project (3GPP) LTE and 5G new radio (NR), Wi-Max, IEEE 802.11p, and IEEE 802.16e [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been going on with the suitability of different wireless technologies for V2X communication. Few researchers have suggested medium and long-range low-power wireless technologies like long range (LoRa) communication, Zigbee, BLE, and WIFI [11][12][13] On the other hand, researchers have adopted wireless technologies such as the Third Generation Partnership Project (3GPP) LTE and 5G new radio (NR), Wi-Max, IEEE 802.11p, and IEEE 802.16e [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the proposed protocol gives optimum performance under the defined scenario and assumptions being made. In Table 4, we expand the security performance analysis for some more available schemes [43][44][45] and tabulate the findings. Such an analysis is believed to help future researchers to identify the protocols specific to their area of study.…”
Section: Discussion and Comparative Summarymentioning
confidence: 99%
“…In principle, VNDN can operate in presence of multiple wireless access standards, including the most prominent alternatives for vehicular networks, namely IEEE 802.11p and Cellular Vehicle to Everything (C-V2X) [16]. In the following, however, we mainly refer to vehicular ad hoc networks (VANETs) based on IEEE 802.11p, which is the reference technology in almost all the VNDN-based solutions available in the literature [14].…”
Section: Vehicular Ndnmentioning
confidence: 99%